Diagnostic dilemma of proximal ulnar artery aneurysm - Vinojan Satchithanantham, MD, FRCS(Ed); Mohamed Banihani, MD, FRCS(Ed) (Radiology Case Reports, 2023)
A 67-year-old lady presented to the vascular clinic with (8 × 4) cm pulsatile swelling in her right medial forearm and had congenital high-flow AV fistula in the same arm ligated in the antecubital fossa 2 years earlier. MR angiogram failed to make a definitive diagnosis and conventional angiogram was also inconclusive. As she became more symptomatic consequently, underwent surgical procedures. The finding was a large proximal ulnar artery aneurysm. The aneurysm was excised and artery was ligated. Proximal ulnar artery aneurysms are rarely reported in the literature. Thus, this case presents a diagnostic challenge in persistent flow despite the large thrombus.